تعليميّة الدّرس البلاغي في الطّور الثّانوي مقاربة تداوليّة - الايجاز أنموذجا- - عبد القادر, عزوز; مصطفى, غربي (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدّراسة إلى مقاربة المفاهيم والأفكار التي انتهى إليها الدّرس التّداولي الحديث من زاوية إجرائيّة عمليّة من خلال إخضاع النّصوص للتّحليل والتّطبيق، خاصّة في ظلّ الزّخم المعرفيّ النّظري الذي أصبحت تشهده ساحة الدّراسات اللّغويّة، ومن زاوية أخرى ارتأينا أن ندمج أهمّ إجراءات المنهج التّداولي العمليّة في حقل تعليمية اللّغة عامّة والبلاغة خاصّة، لما يوجد من ترابط وتقاطع بينهما، حيث تقف هذه الأخيرة على القوانين التي تحكم عمليّة الخطاب، لتسهّل بذلك عمليّة التّواصل بين عناصر العمليّة التّعليمية التّعلمية. The study aims at the approximation of the concepts and the ideas that the modern pragmatic study has issued from a workable procedure side, by subjugation the texts to the analysis and the application, specially under the theoretical cognitive momentum which the arena of linguistic stidies are witnessing them. From another side, we decided to integrate the most important practical deliberative approache procedures in the field of language education in general and rhetoric in particular due to the interconnectedness and intevsection between them, as the latter stands on the laws that govern the speech process to facilitate the process of communication between the elements of the educational learning process.
مقال
Keywords: التّعليمية ; البلاغة ; التّداولية ; العلاقة ; الايجاز